2018
DOI: 10.1200/jco.2018.78.5865
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients With Progressive Midgut Neuroendocrine Tumors Treated With 177Lu-Dotatate in the Phase III NETTER-1 Trial

Abstract: Purpose Neuroendocrine tumor (NET) progression is associated with deterioration in quality of life (QoL). We assessed the impact of Lu-Dotatate treatment on time to deterioration in health-related QoL. Methods The NETTER-1 trial is an international phase III study in patients with midgut NETs. Patients were randomly assigned to treatment withLu-Dotatate versus high-dose octreotide. European Organisation for Research and Treatment of Cancer quality-of-life questionnaires QLQ C-30 and G.I.NET-21 were assessed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
226
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(242 citation statements)
references
References 16 publications
8
226
1
7
Order By: Relevance
“…The results herein indicate that first-line treatment tended to be less aggressive, resulting in more frequent first-line treatment with SSA and less frequent first-line chemotherapy, even though the disease seems to be at least as aggressive as that in younger patients. In addition, the present study found that during the course of their disease older patients had less frequently PRRT, a treatment that has shown a benefit in terms of survival and quality of life [21,22]. Elderly patients also received less frequently targeted therapy, another treatment that improves efficacy, which could be given at appropriate adapted doses depending on comorbidities [15,16].…”
Section: Discussionmentioning
confidence: 55%
“…The results herein indicate that first-line treatment tended to be less aggressive, resulting in more frequent first-line treatment with SSA and less frequent first-line chemotherapy, even though the disease seems to be at least as aggressive as that in younger patients. In addition, the present study found that during the course of their disease older patients had less frequently PRRT, a treatment that has shown a benefit in terms of survival and quality of life [21,22]. Elderly patients also received less frequently targeted therapy, another treatment that improves efficacy, which could be given at appropriate adapted doses depending on comorbidities [15,16].…”
Section: Discussionmentioning
confidence: 55%
“…In the recently updated NETTER-1 trial, a mOS of 27.4 months was reported for the octreotide arm and had still not been reached in the 177 Lutetium-PRRT arm, suggesting a significant benefit in the quality of life of patients with progressive midgut neuroendocrine tumors [7,8] In previous studies, mOS from the start of treatment was 46 months and 128 months from diagnosis compared with historical controls, revealing a survival benefit of 40-72 months from diagnosis. [9] These findings highlight the impact of PRRT treatment on patient outcome; especially of older patients whose shorter life expectancy and comorbidities can affect access to this treatment in a second-or-further-line setting.…”
Section: Karger@kargercommentioning
confidence: 99%
“…More than 20 y after the pioneering work in isolated centers in Europe such as Rotterdam, Basel, and Milan, PRRT with radiolabeled sstr agonists (e.g., DOTATOC or DOTATATE, Table 2) is part of the standard of care for NENs (4). Recently, the randomized phase III study NETTER-1 showed an improved objective response, an improved quality of life, improved progressionfree survival, and a clear trend toward an overall survival benefit from PRRT with 4 cycles of 177 Lu-DOTATATE (plus long-actingrelease single-dose octreotide) compared with long-acting-release double-dose octreotide alone (5,6). Consequently, 177 Lu-DOTA-TATE ( 177 Lu-oxodotreotide) received marketing authorization for patients with metastatic and progressive midgut NEN.…”
Section: Somatostatin In Nen and Beyondmentioning
confidence: 99%